Adulting follies - Chen, Jingyi (Nanyang Technological University, 2021)
In the journey of education, every student is presented with an opportunity to broaden their knowledge through an overseas exchange program. Besides circularly, the program provides networking and cultural insights not found locally. Though it is all fun and games in the picture, the journey is fueled with challenges and uncertainties as far as life-changing experiences go. Built on individual adaptation, one must overcome the difficulties and adjust to cultural differences. Past that, the perception of the World changes significantly as you rediscover knowledge and the personal direction in life. This project aims to produce an editorial publication that would inspire students who are planning to go on an exchange programme. “Adulting Follies” is a soul searching and stress-inducing piece which features personal documentation of an individual's self-reflection of the exchange program to Canada. It seeks to help students have a deeper understanding and an easier way to concoct their unique exchange program experience.